Synthesis and catalytic activity of monodisperse gold-mesoporous silica core-shell nanocatalysts - Sekhar, A. C. Sunil; Meera, C. J.; Kottavarithottil Ziyad; Gopinath, Chinnakonda S.; Vinod, C. P. (Catalysis Science & Technology, 2013)
Core-shell nanostructures, where gold nanoparticles of sub 10 nm size are successfully encapsulated inside porous silica spheres, have been prepared. The detailed characterization of the catalyst shows a high surface area and good mesoporosity. The sinter resistance of the catalyst under repeated cycles of the CO oxidation reaction is observed.